Hypertension and hyperglycemia and the combination thereof enhances the incidence of chronic kidney disease (CKD) in middle-aged and older males. (3rd October 2017) - Michishita, Ryoma; Matsuda, Takuro; Kawakami, Shotaro; Tanaka, Satoshi; Kiyonaga, Akira; Tanaka, Hiroaki; Morito, Natsumi; Higaki, Yasuki
ABSTRACT: Aim : Chronic kidney disease (CKD) may be an etiologic cause of aging, hypertension, diabetes mellitus (DM), and metabolic syndrome. However, the influence of these cardiovascular risk factors and their combination on the development of CKD remains controversial. This retrospective study evaluated the influence of cardiovascular risk factors and their combination on the incidence of CKD during a 6-year follow-up period in middle-aged and older males. Methods : The subjects were 303 males without a history of cardiovascular disease, stroke, renal dysfunction, or dialysis treatment. A biochemical analysis, blood pressure (BP) analysis, and anthropometry measurements were performed every year, and the classification of CKD was also assessed based on the estimated glomerular filtration rate (<60 ml/min/1.73 m 2 ) and/or presence of proteinuria. Results : After 6 years, the incidence of CKD was noted in 32 subjects. According to a multivariable analysis, hypertension (hazard ratio [HR]: 3.95, 95% confidence of interval [CI]: 1.64–9.49, p = 0.002) and hyperglycemia (HR: 3.27, 95% CI: 1.42–7.56, p = 0.006) were significantly associated with the incidence of CKD. According to a Cox proportional hazards model, the HR for the incidence of CKD was significantly higher in the combination of high-normal BP /hypertension and impaired fasting glucose/DM group than in the combination of normotensive and normal glucose tolerance group (HR: 7.16, 95% CI: 2.43–17.25, p = 0.001). Conclusions : These results suggest that the hypertension and hyperglycemia and their combination may be associated with the incidence of CKD.